Leader personality and employees' experience of workplace stressors. Issue 3 (29th August 2014) - Robertson, Ivan; Healey, Mark; Hodgkinson, Gerard P; Flint-Taylor, Jill; Jones, Fiona; Sparrow, Paul; Sparrow, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose To explore relationships between leader personality traits (neuroticism and conscientiousness) and four specific workplace stressors (control; work overload; work-life balance and managerial relationships) experienced by work group members. Design/methodology/approach We accessed personality data from N= 84 leaders and surveyed members of their respective work groups (N = 928) to measure established workplace stressors. Multi-level modelling analyses were conducted to explore relationships between leader neuroticism and conscientiousness and work group members' perceptions of sources of pressure. Findings Our results relate to the general problem of how, and to what extent leaders have an impact on the well-being of members of their workgroups. Although previous research has generally associated conscientiousness with effective leadership, our results suggest that some facets of conscientiousness may be less useful for leadership effectiveness than others. In particular, the results show that leaders' levels of achievement striving are linked to poor work life balance scores for their workgroups. The results also show that leader neuroticism is not related to work group members' perceptions of sources of pressure. Practical implications Our findings showed that leader personality influences three out of the four employee stressors hypothesized. The idea that the influence of leader personality may be relatively indirect via employee working conditions is potentially important and suggests implications for practice. To the extent that the negative effects of leader personality are mediated via working conditions, it may be feasible to counter, or at least assuage such effects by implementing appropriate regulations or working practices that mitigate leaders' ability to influence the specific conditions in question. Originality/value Most studies have focused on how employee well-being outcomes are influenced through the direct impacts of leadership styles and behaviours, or contagious emotions. We explore an alternative and untested proposition that the leaders' personality influences the working conditions that are afforded to subordinates. No empirical research to date has examined the relationships between leader personality and workplace stressors. The research also demonstrates the importance of using facet-level personality measures, compared with measures at the broad domain level.